Tlingit women pose in ceremonial dress, Alaska, ca. 1910-1923. - Andrews, Clarence Leroy, 1862-1948
Women pose in street. They wear embroidered, beaded & button tunics over dresses, and headdresses. Woman in back has a Chilkat blanket over dress and a carved wooden headdress. Row of buildings visible in background. Note from unidentified source: Possibly Hoona